Eksistensi Hak Kebebasan Berpendapat Terkait Mengkritik Kebijakan Pemerintah Yang Terancam Oleh UU ITE - Pangaribuan, Safana Aprilya (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2023)
Freedom of speech is the right for every human being or individual to speak freely for his or her opinion, and is included in the classification of personal rights in human rights. So the right to freedom of opinion is part of one of the human rights that relates to a person's personality. The purpose of this research is to find out the existence of the right to freedom of speech in criticizing government policies which in reality are limited by the ITE Law. The method used in this research is normative law by collecting primary and secondary data from regulations, books, journals, and documents related to the research. The results of this study found several cases related to the right to freedom of speech that is restricted by Law Number 19 of 2016 concerning Electronic Information and Transactions Law.